Transcriptional Attenuation Controls Macrolide Inducible Efflux and Resistance in Streptococcus pneumoniae and in Other Gram-Positive Bacteria Containing mef/mel(msr(D)) Elements - Chancey, Scott T.; Bai, Xianhe; Kumar, Nikhil; Drabek, Elliott F.; Daugherty, Sean C.; Colon, Thomas; Ott, Sandra; Sengamalay, Naomi; Sadzewicz, Lisa; Tallon, Luke J.; Fraser, Claire M.; Tettelin, Hervé; et al. (PloS one, 2015)
Macrolide resistance, emerging in Streptococcus pneumoniae and other Gram-positive bacteria, is increasingly due to efflux pumps encoded by mef/mel(msr) operons found on discrete mobile genetic elements. The regulation of mef/mel(msr) in these elements is not well understood. We identified the mef(E)/mel transcriptional start, localized the mef(E)/mel promoter, and demonstrated attenuation of transcription as a mechanism of regulation of macrolide-inducible mef-mediated macrolide resistance in S. pneumoniae. The mef(E)/mel transcriptional start site was a guanine 327 bp upstream of mef(E). Consensus pneumococcal promoter -10 (5'-TATACT-3') and -35 (5'-TTGAAC-3') boxes separated by 17 bp were identified 7 bp upstream of the start site. Analysis of the predicted secondary structure of the 327 5' region identified four pairs of inverted repeats R1-R8 predicted to fold into stem-loops, a small leader peptide [MTASMRLR, (Mef(E)L)] required for macrolide induction and a Rho-independent transcription terminator. RNA-seq analyses provided confirmation of transcriptional attenuation. In addition, expression of mef(E)L was also influenced by mef(E)L-dependent mRNA stability. The regulatory region 5' of mef(E) was highly conserved in other mef/mel(msr)-containing elements including Tn1207.1 and the 5612IQ complex in pneumococci and Tn1207.3 in Group A streptococci, indicating a regulatory mechanism common to a wide variety of Gram-positive bacteria containing mef/mel(msr) elements.